Komunikasi Negosiasi Dalam Adat Pisuke Pada Masyarakat Selong Belanak - Hendayani, Baiq (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
process communication negotiation tradition pisuke is things to do when wedding happen . Communication negotiation pisuke this Becomes bridge for second bride for carry on contract wedding . If communication negotiation pisuke this conducted by second split party family with method hard or no be patient , then for get say agreed can caused difficult , however on the contrary if conducted with You're welcome patient as well as enclose on interest together no on interest personal so no close possibility that say agreed will with easy can achieved . Then Destination from study this is for understand How communication negotiation in tradition pisuke on Public village Selong Mullet Central Lombok Regency . Method study this use approach qualitative . Which data source used is primary type data source with interview by direct to a number of subjects as research data sources , other data sources is secondary that is with review article in journal as well as book in support study this . Results study this is communication carried out by second split party conducted that is each from they will do it with follow process communication negotiation with patient so that process obtained _ fast find say deal and process wedding the fast for implemented , communication initiated _ with opening , process negotiation and cover . That on process communication this could conducted one , two , three even until four times, according to results from Interview can reach a month if the communication tough , and the longest is a month half .